Women at the center : Grameen Bank borrowers after one decade - Todd, Helen, 1943- (University Press, 1996)
For two decades, the Grameen Bank of Bangladesh has successfully administered a unique program that lends small sums to poor women for income generation. This is the first empirical study to examine the long-term influence of these loans on the borrowers, and it demonstrates that credit alone can fundamentally change the lives of poor women - even in the absence of other aid programs and in an environment distinctly hostile to women's autonomy.